"To Rule And Own, Or To Live Like Shy Deer": The Dilemmas of a Profession (1) - Louw, Johann (PINS-Psychology in Society, 2026)
At its 1989 and 1990 annual conferences, the Psychological Association of South Africa (PASA), showed the clearest evidence a yet of going through a process of self-examination as a result of changing political realities in this country. At the 1990 conference, this was operationalized a need to restructure the Association to provide a home for all South African psychologists. Without negating the debates conducted al these annual meetings, I believe, however, that there is an underlying, deeper issue at stake here. For me, this is related to the process of professionalization (2). Since the essay is not intended as a conceptual analysis of what a profession is, I shall simply use the definition given by Abbott (1988): " ... professions are exclusive occupational groups applying somewhat ab tract knowledge to particular cases" (p8). By extension, professionalization then is the process via which the occupational group establishes its exclusivity over a specific knowledge domain (see J. Louw, 1990, pl4 for a definition of the professionalization of psychology). Professionalization can be examined at a number of levels of abstraction. For example: in terms of the role of intellectuals in society, or in terms of the division of expert labour in society. At a somewhat less abstract and more empirical level one might consider the process of professionalization as it unfolds in a particular occupation. At a fairly concrete level, one might examine practical measures a profession has at its disposal to advance its position vis-a-vis other professions, or to provide better services in society. Given the context of this essay, it treats the topic at fairly concrete levels of analysis. The discussion opens with two theses, which are essential to clarify the contentions made subsequently. These take the form of ten practical suggestions as to how the profession might respond to its current dilemmas.